A silica singmode fibre-chalcogenide multimode fibre-silica singlemode fibre structure - Wang, Pengfei; Ding, Ming; Bo, Lin; Semenova, Yuliya; Wu, Qiang; Farrell, Gerald (Photonics Letters of Poland, 2012)
In this letter we theoretically and experimentally investigate a singlemode-multimode-singlemode (SMS) structure based on chalcogenide (As2S3) multimode fibre and silica singlemodefibres. The experimental results show a general agreement with the numerical simulation results based on a wide angle-beam propagation method (WA-BPM). Multimode interference variation was observed as a result of photo-induced refractive index changes arising from either localized laser irradiation at a wavelength of 405 nm or the use of a UV lamp. Our result provides a platform for the development of compact, high-optical-quality, and robust photonic nonlinear devices. Full Text: PDF References Q. Wu, Y. Semenova, P. Wang, A. M. Hatta and G. Farrell, "Experimental demonstration of a simple displacement sensor based on a bent single-mode?multimode?single-mode fiber structure ", Meas. Sci. Technol., 22, 025203 (2011). CrossRef S. M. Tripathi, A. Kumar, R. K. Varshney, Y. B. P. Kumar, E. Marin, J.-P. Meunier, "Strain and Temperature Sensing Characteristics of Single-Mode?Multimode?Single-Mode Structures", J. Lightwave Tech., 27, 2348 (2009). CrossRef P. Wang, G. Brambilla, M. Ding, Y. Semenova, Q. Wu, G. Farrell, "High-sensitivity, evanescent field refractometric sensor based on a tapered, multimode fiber interference", Opt. Lett., 36, 2233 (2011). CrossRef Q. Wang and G. Farrell, "Multimode-fiber-based edge filter for optical wavelength measurement application and its design", Micro. Opt. Tech. Lett., 48, 900 (2006). CrossRef C. Grillet, S. N. Bian, E. C. Magi, and B. J. Eggleton, "Fiber taper coupling to chalcogenide microsphere modes ", Appl. Phys. Lett., 92, 171109 (2008). CrossRef Masaki Asobe, Hideki Kobayashi, Hiroki Itoh, and Terutoshi Kanamori, "Laser-diode-driven ultrafast all-optical switching by using highly nonlinear chalcogenide glass fiber", Opt. Lett., 18, 1056 (1993). CrossRef S. Shakeri and M. Hatami, "Self-tunable chalcogenide Raman laser", J. Opt. Soc. Am. B, 27, 679 (2010). CrossRef B. J. Eggleton, B. Luther-Davies, and K. Richardson, "Chalcogenide photonics", Nature Photonics, 5, 141 (2011). CrossRef P. Wang, G. Brambilla, M. Ding, Y. Semenova, Q. Wu, G. Farrell, "Investigation of single-mode?multimode?single-mode and single-mode?tapered-multimode?single-mode fiber structures and their application for refractive index sensing", J. Opt. Soc. Am. B, 28, 1180 (2011). CrossRef